Victimization by stalking: predictors of fear - Matos, Marlene (2012)
This paper aims to reflect about a reality that is still hidden in the national context - stalking - and to analyze the factors that compete to fear as a result of this kind of victimization. The study was conducted with a sample of 236 participants that had reported being a target of stalking in some point of their lives. Victim's age, sex, and also being victim of surveillance by the stalker have emerged as predictors of fear as a consequence of stalking. Therefore, results suggest that the effects of this type of violence should be understood and located in the sociocultural tissue, being necessary a greater investment in research and practices for acting against this phenomenon.